The mysterious abductions - Hecht, Tracey (Hecht, Tracey. Nocturnals, 2016)
Three unlikely nocturnal animal friends--Dawn the fox, Tobin the pangolin, and Bismark the sugar glider--form a brigade of the night to look into the mysterious disappearance of animals.